Responsive Parenting Behaviors and Cognitive Function in Children With Sickle Cell Disease. (3rd October 2019) - Yarboi, Janet; Prussien, Kemar V; Bemis, Heather; Williams, Ellen; Watson, Kelly H; McNally, Collen; Henry, Lauren; King, Allison A; DeBaun, Michael R; Compas, Bruce E
Abstract: Objective: Children with sickle cell disease (SCD) are at increased risk for cognitive impairment as a result in part from biological characteristics of the disease; however, limited research has explored possible social and contextual factors associated with risk for cognitive problems. The primary aim of the present study was to examine the relation between children's cognitive functioning and responsive parenting, a potentially important contextual factor in children with SCD, accounting for family socioeconomic disadvantage, child disease severity, and caregivers' perceived stress. Methods: Forty-eight children completed standardized cognitive assessments and caregivers provided self-reports of general and disease-related stress. Parent–child dyads completed a video recorded puzzle-solving task and observed parenting was quantified using two coding systems. Bivariate Pearson correlations were used to assess preliminary hypotheses, and linear multiple regression analyses were used to assess the primary hypothesis. Results: Results suggested that increased levels of parental stress were related to fewer observations of responsive parenting and provided evidence of an association between children's cognitive function and responsive parenting. Specifically, increased disease-related parent stress and reduced parental use of expansive language were associated with significantly lower cognitive functioning in children with SCD. Conclusions: Findings suggest that social environmental factors along with disease characteristics are sources of risk for cognitive problems with children with SCD. Further, these findings highlight the need to develop targeted interventions for parents of children with SCD to decrease levels of stress and enhance parenting skills, with the aim improving cognitive functioning in youth.